Meningkatkan Motivasi Belajar Siswa Sekolah Dasar Dalam Pelajaran Pkn Melalui Model Pembelajaran Kooperatif Tipe Team Game Tournament - Afriza Anggita Devy (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The purpose of this study was to increase students' learning motivation in Pancasilasubject matter PKN lessons by using the Cooperative Model Type Team GameTournament. The research method used is Classroom Action Assessment (CAR) whichconsists of 3 cycles and each cycle consists of stages of planning, action, observation andreflection activities. Based on the implementation of the Team Game Tournamnet Model,to increase students' learning motivation, students get learning outcomes, namely Cycle Iwith an average of 59.4 because students are still not familiar with the TGT Model. Theincrease in the acquisition of learning outcomes occurs in Cycle II with an average of 68.6because students have started interested in the TGT Model and enthusiastic aboutparticipating in learning, In Cycle III there was a significant increase with evidence ofobtaining learning outcomes with an average of 88.7 because students were used to the funTGT Model and significantly increased learning motivation. So it can be said that theapplication of the Team Game Tournament Model in PKN lessons on Pancasila materialcan increase student motivation and enthusiasm.